Development and human rights in Ethiopia: taking the constitutional right to development seriously - Sisay, Yonas Tesfa (2015)
This thesis examines the nature, content and legal implications of the constitutional right to development and investigates its (non-)realization by inquiring how development and human rights are being pursued in Ethiopia. In addressing these issues, this study analytically situates the conception of the right to development as enshrined in the Federal Democratic Republic of Ethiopia (FDRE) Constitution within the context of the general human rights and development debates, the normative framework of the right to development as established by the United Nations Declaration on the Right to Development (UNDRD) and the African Charter on Human and Peoples Rights (ACHPR). Thus, it discusses the theoretical and moral basis for linking development and human rights and conceptualizing the claim for development as a distinct human right. It further explores the evolution of the right to development into an international human rights norm and addresses its attendant controversies. It subsequently analyses the nature and content of the right to development as established under the UNDRD and ACHPR before engaging with the issues relating to the FDRE Constitution. This research has employed doctrinal and comparative legal research methodologies and also involved critical analysis of policy documents and data from secondary sources. This research finds that the right to development as enshrined in the FDRE Constitution is enunciated in ambiguous terms and asserts that it needs to be understood within the broader constitutional context of Ethiopia which, in conformity with UNDRD and ACHPR, considers development and human rights to be interdependent and mutually reinforcing projects which can only be realized through such interdependence and mutuality. It further submits that the constitutional right to development generally provides a legally binding normative framework within which development processes in Ethiopia should be pursued and puts a constitutional limit on the power of the State as it relates to development undertakings. It, however, identifies that, despite its legally binding nature, the observance of this right is not provided with effective guarantee (enforcement mechanism) as the Ethiopian courts are excluded from enforcing constitutional human rights. This study also claims that the realization of the constitutional right to development has been impeded by the governing ideologies of revolutionary democracy and developmental state which undermine the basic conditions necessary for undertaking development and human rights as interdependent and mutually reinforcing goals of the Constitution. Its review of Ethiopia’s successive development policies reveals the marginal importance given to human rights in general and the two fundamental aspects of the constitutional right to development – the right to active, free and meaningful participation in development and the right to fair distribution of the benefits of development – in particular. Its assessment of Ethiopia’s balance sheet of socio-economic development and human rights in the last decade also attests that development and human rights have been practically disentangled and signals the need for taking the constitutional right to development seriously.